The Effect Of Knowledge Management, Skills, And Attitude On Employee Performance Mediated By Professionalism - Prasetya, Dwi Jaka; Abd , Tengku Mohd. Kharil (Asian Journal of Social and Humanities, 2025)
This study aims to examine the effect of knowledge management, skills, and attitude on employee performance with professionalism as a mediating variable. In the current era of dynamic organizational competition, effective knowledge management, adequate skills, and positive employee attitudes are crucial factors in improving performance outcomes. However, these factors often require the presence of professionalism to optimize their influence on organizational effectiveness. This research employs a quantitative approach by distributing structured questionnaires to employees within the organization. Data were analyzed using statistical techniques to test both direct and indirect relationships among variables. The findings reveal that knowledge management, skills, and attitude significantly enhance employee performance. Furthermore, professionalism plays a mediating role, strengthening the effect of these independent variables on performance. This indicates that employees with strong professionalism are better able to apply their knowledge, utilize their skills, and maintain a positive attitude, which in turn leads to improved performance. The study contributes to the development of human resource management strategies by highlighting the importance of professionalism in maximizing employee potential. Practically, organizations are encouraged to foster professionalism through training, mentoring, and cultural reinforcement programs to sustain competitive advantage.